PERENCANAAN PRODUKSI AGREGAT BERDASARKAN PENDEKATAN OPTIMASI PROGRAMA LINIER DI PERUSAHAAN SEPATU OLAH RAGA - Sulistyadi, Kohar; Saputro, Firdhaus Hari; Himawan, Pandu (JURNAL GAUNG INFORMATIKA, 2013)
Effort to minimize the cost of production companies in an effort to increase competitive advantage through a number of ways to implement strategies to meet theminimum production costs demand. In this research is focused on aggregate production planning through several stages, namely: (1) forecasting product demand in the coming year, (2) aggregate production planning with reference to